An Integrated Molecular Approach to Untangling Host–Vector–Pathogen Interactions in Mosquitoes (Diptera: Culicidae) From Sylvan Communities in Mexico - Hernández-Triana, Luis M.; Garza-Hernández, Javier A.; Ortega Morales, Aldo I.; Prosser, Sean W. J.; Hebert, Paul D. N.; Nikolova, Nadya I.; Barrero, Elsa; de Luna-Santillana, Erick de J.; González-Alvarez, Vicente H.; Mendez-López, Ramón; Chan-Chable, Rahuel J.; Fooks, Anthony R.; et al. (Frontiers in Veterinary Science, 2021)
There are approximately 240 species of Culicidae in Mexico, of which some are vectors of arthropod-borne viruses such as Zika virus (ZIKV), Dengue virus (DENV), Chikungunya virus (CHIKV), and West Nile virus (WNV). Thus, the identification of mosquito feeding preferences is paramount to understanding of vector-host-pathogen interactions that, in turn, can aid the control of disease outbreaks. Typically, DNA and RNA are extracted separately for animal (insects and blood meal hosts) and viral identification, but in this study, it is shown that all three organisms can be analyzed from a single RNA extract. Residual DNA present in standard RNA extracts was analyzed by DNA barcoding in concert with Sanger and next-generation sequencing (NGS) to identify both the mosquito species and the source of their meals in blood-fed females caught in seven sylvan communities in Chiapas State, Mexico. The same RNA extract was used to screen for the presence of arboviruses. In total, 14 genera, 25 subgenera, and 61 morphospecies of mosquitoes were collected. Of these, four species were new records for Mexico (Aedes guatemala, Ae. insolitus, Limatus asulleptus, Tr. pallidiventer), and nine were new records for Chiapas State. DNA barcode sequences for >300 bp of the COI gene were obtained from 291 specimens while 130 bp sequences were recovered from another 179 specimens. High intra-specific divergence values (>2%) suggesting cryptic species complexes were observed in nine taxa: Anopheles eiseni (5.39%), An. pseudopunctipennis (2.79%), Ae. podographicus (4.05%), Culex eastor (4.88%), Cx. erraticus (2.28%), Toxorhynchites haemorrhoidalis (4.30%), Tr. pallidiventer (4.95%), Wyeomyia adelpha/Wy. guatemala (7.30%) and Wy. pseudopecten (4.04%). The study raised the number of mosquito species known from to 148 for Chiapas State and to 238 for Mexico. Blood meal analysis showed that Aedes angustivittatus fed on ducks and chicken, while Psorophora albipes fed on humans. Culex quinquefasciatus fed on diverse hosts including chicken, human, turkey, and Mexican grackle. No arbovirus RNA was detected by RT-PCR in the surveyed specimens. This study demonstrated the important role of molecular approaches in both vector identification and revealing host-vector-pathogen interactions.